Preobrazba naselja i socijalno prestrukturiranje stanovništva Hrvatskog zagorja : doktorska disertacija - Njegač, Dražen (D. Njegač, 1995)
Summary: During the last thirty years, Hrvatsko zagorje has experienced a radical socio-economic transformation, from the rural intothe urbanized province, reflecting particulary changes in the social structure of the population and in transformation of settlementes. The most influential processes are de-agrarization and urbanization. The essential reference point for social re-structuring of population in the agrarian regions is transition of population from agriculture to non- agriculturalactivities. Decreaseof agricultural population and of its proprotion within total population is one of the most significant indicators of de-agrarization.